ByzRev 06.2024.057: Fabian Stroth, The Church of St. Polyeuktos at Constantinople: (Elements in the History of Constantinople). Cambridge: Cambridge University Press 2024 - Makris, Georgios (The Byzantine Review, 2024)
Fabian Stroth, The Church of St. Polyeuktos at Constantinople (Elements in the History of Constantinople). Cambridge: Cambridge University Press 2024. 4, 82 pp. – ISBN 978-1-009-51706-5